Thorea indica sp. nov. (Thoreales, Rhodophyta) from Uttar Pradesh, India - Necchi, Orlando [UNESP]; Paiano, Monica O. [UNESP]; West, John A.; Ganesan, E. K.; De Goër, Susan Loiseaux (The Korean Society of Phycology, 2015)
Thorea indica sp. nov. is described from the Sai River, Uttar Pradesh, India (26°39’00.7” N, 80°47’38.3” E). Its classification is based on molecular sequences of the plastid-encoded RuBisCO large-subunit gene, rbcL and the barcode region of the mitochondrial encoded cytochrome c oxidase subunit 1, cox1, and morphological data. The sequence analyses confirm a new species of Thorea. The cox1 barcode sequence had 90.4-90.8% identity with Thorea sp. from Australia and Thorea hispida from Hawaii and China. Based on rbcL sequences the Indian specimen was positioned in a major clade with high support (>95 bootstrap and 0.95 posterior probability) containing two other species: T. okadae from Japan and T. hispida from the continental USA, Hawaii, the UK, and China. The divergences among these sequences were T. indica vs. T. okadae (2.8%) and T. indica vs. T. hispida (2.9-3.4%). The comparison of morphological characters of Thorea from India was not conclusive due to the inadequate descriptions in previous reports: most specimens reported as T. hispida fit within the circumscription of T. indica as described here. The previous report of T. siamensis from the Sai River is incorrect and the specimens fit within our description of T. indica. Thorea indica and T. okadae can be distinguished by minor morphometric characters and sexuality (dioecious vs. monoecious).
Keywords: Cox1; India; Molecular systematic; Morphology; RbcL; Reproduction; Thorea indica sp. nov; Thoreales